2016
DOI: 10.1080/0144929x.2016.1232754
|View full text |Cite
|
Sign up to set email alerts
|

Exploring educational immersive videogames: an empirical study with a 3D multimodal interaction prototype

Abstract: Gestural interaction devices emerged and originated various studies on multimodal human-computer interaction to improve user experience. However, there is a knowledge gap regarding the use of these devices to enhance learning.We present an exploratory study which analysed the user experience with a multimodal immersive videogame prototype, based on a Portuguese historical/cultural episode. Evaluation tests took place in high school environments and public videogaming events. Two users would be present simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Findings like these all point towards the affordances of immersive technologies such as HMDs. This however, is somewhat contrasted by Fernandes et al (2016), who found that increasing immersion by adding 3D sounds and a graphical rendering of user's own hands to the virtual environment confused some study participants and distracted from the learning task.…”
Section: The Influence Of Immersion and Presence On Learningmentioning
confidence: 90%
See 4 more Smart Citations
“…Findings like these all point towards the affordances of immersive technologies such as HMDs. This however, is somewhat contrasted by Fernandes et al (2016), who found that increasing immersion by adding 3D sounds and a graphical rendering of user's own hands to the virtual environment confused some study participants and distracted from the learning task.…”
Section: The Influence Of Immersion and Presence On Learningmentioning
confidence: 90%
“…Of the 21 studies 14 examined the learner experience (Andreoli et al, 2016;Bharathi & Tucker, 2015;Fernandes et al, 2016;Gutiérrez-Maldonado, Ferrer-García, Plasanjuanelo, Andrés-Pueyo, & Talarn-Caparrós, 2015;Janssen, Tummel, Richert, & Isenhardt, 2016;Kleven et al, 2014;Loup, Serna, Iksal, & George, 2016;Madrigal, Prajapati, & Hernandez-Prera, 2016;Moesgaard et al, 2015;Pan et al, 2016;Polcar & Horejsi, 2015;Ray & Deb, 2016;Reiners, Wood, & Gregory, 2014;Stavroulia et al, 2016). The main aspects of learner experience being examined in the included studies can be divided into three groups, namely: (1) Perceived presence, immersion and realism;…”
Section: Selection Processmentioning
confidence: 99%
See 3 more Smart Citations